Extra-long G alpha s Variant XL alpha s Protein Escapes Activation-induced Subcellular Redistribution and Is Able to Provide Sustained Signaling - (:unkn) unknown (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2011)
Murine models indicate that G alpha s and its extra-long variant XL alpha s, both of which are derived from GNAS, markedly differ regarding their cellular actions, but these differences are unknown. Here we investigated activation-induced trafficking of G alpha s and XL alpha s, using immunofluorescence microscopy, cell fractionation, and total internal reflection fluorescence microscopy. In transfected cells, XL alpha s remained localized to the plasma membrane, whereas G alpha s redistributed to the cytosol after activation by GTPase-inhibiting mutations, cholera toxin treatment, or G protein-coupled receptor agonists (isoproterenol or parathyroid hormone (PTH)(1-34)). Cholera toxin treatment or agonist (isoproterenol or pituitary adenylate cyclase activating peptide-27) stimulation of PC12 cells expressing G alpha s and XL alpha s endogenously led to an increased abundance of G alpha s, but not XL alpha s, in the soluble fraction. Mutational analyses revealed two conserved cysteines and the highly charged domain as being critically involved in the plasma membrane anchoring of XL alpha s. The cAMP response induced by M-PTH(1-14), a parathyroid hormone analog, terminated quickly in HEK293 cells stably expressing the type 1 PTH/PTH-related peptide receptor, whereas the response remained maximal for at least 6 min in cells that co-expressed the PTH receptor and XL alpha s. Although isoproterenol-induced cAMP response was not prolonged by XL alpha s expression, a GTPase-deficient XL alpha s mutant found in certain tumors and patients with fibrous dysplasia of bone and McCune-Albright syndrome generated more basal cAMP accumulation in HEK293 cells and caused more severe impairment of osteoblastic differentiation of MC3T3-E1 cells than the cognate G alpha s mutant (gsp oncogene). Thus, activated XL alpha s and G alpha s traffic differently, and this may form the basis for the differences in their cellular actions.
Keywords: STIMULATORY G-PROTEIN; MCCUNE-ALBRIGHT-SYNDROME; GNAS1 T393C POLYMORPHISM; PARATHYROID-HORMONE RECEPTOR; COUPLED RECEPTORS; ADENYLYL-CYCLASE; CELL CARCINOMA; FREE SURVIVAL; GENE VARIANT; SUBUNIT